Model of nurses' perception of the critically ill patients' transition experience - Mohamed Ludin, Malaysia (2019)
Background A conceptual model representing nurses' perceptions of the transition experience has been developed to summarise interpretation of the study's findings and provide a conceptual understanding of the transition process. The model illustrates the transition process as experienced by the critically ill patients and their families, nurses' understanding of transition and their response to the patients' and families' experience. Justification The transition process is seen as three interrelated transition processes (Figure 1) Continuous transition process. Patients' and families' transition experience. Nurses'response. This model is compared with two other conceptual models-'Transition Theory' by Schlossberg (1981) (see Figure 8.2 next page) and'ExperiencingTransition: Middle RangeTheory'by Meleis et al. (2000) to distinguish the simllarities and differences of the components of transition.